Funerals, memorials and bereavement care. Issue 2 (2nd September 2019) - Rumbold, Bruce; Lowe, Jennifer; Aoun, Samar M
ABSTRACT: A population survey finds that bereaved people draw upon diverse sources of support in their communities, from both formal services and informal networks of care. The formal service most frequently recognised by participants is provided by funeral directors. We outline some reasons for this, and explore one particular theme, memorialisation, in which funeral providers have traditionally been a lead discipline. Significant changes in memorialisation over recent decades challenge today's funeral industry, but also draw our attention to underlying social changes reshaping our understanding not only of bereavement care but of care in general. Bereavement support is most effective when provided collaboratively by formal and informal care providers, but collaboration is challenged by policies that continue to privilege formal services over informal care. This challenge of developing constructive, respectful and complementary collaborations between formal and informal care is not peculiar to bereavement care, but is a social policy imperative for contemporary societies.